Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan PT Nusantara Bina Diagnostika: The Impact of the Work Environment and Work-Related Stress on Employee Performance at PT Nusantara Bina Diagnostika - Muhammad Alfillail Rasyiq; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
This research was conducted at PT Nusantara Bina Diagnostika Tangerang Selatan, Banten, which is engaged in the distribution sector. The purpose of this study was to analyze the influence of the work environment and work stress on the performance of PT Nusantara Bina Diagnostika employees, both partially and simultaneously. The population in this study were 30 employees of PT Bina Nusantara Diagnostika, using non-probability sampling techniques with a saturated sample method, where the entire population was sampled. Data were analyzed quantitatively using IBM SPSS. Data were collected through questionnaires distributed to respondents. The data analysis method used was multiple linear regression analysis. The results showed that the work environment (X1) had a significant positive effect on employee performance (Y), while work stress (X2) was not significant. Simultaneously, the work environment and work stress had a significant positive effect on performance with a determination coefficient of 0.348, which means that 34.8% of performance is influenced by both variables, while 65.2% by other factors. In conclusion, the work environment has a significant impact on performance, although work stress is not directly significant. Companies are advised to pay attention to the work environment and manage work stress to improve employee performance